Diagnostic accuracy of point-of-care tests for detecting albuminuria: a systematic review and meta-analysis. - McTaggart, M; Newall, R; Hirst, J; Bankhead, C; Lamb, E; Roberts, N; Price, C (2014)
BACKGROUND: Experts recommend screening for albuminuria in patients at risk for kidney disease. PURPOSE: To systematically review evidence about the diagnostic accuracy of point-of-care (POC) tests for detecting albuminuria in individuals for whom guidelines recommend such detection. DATA SOURCES: Cochrane Library, EMBASE, Medion database, MEDLINE, and Science Citation Index from 1963 through 5 December 2013; hand searches of other relevant journals; and reference lists. STUDY SELECTION: Cross-sectional studies, published in any language, that compared the accuracy of machine-read POC tests of urinary albumin-creatinine ratio with that of laboratory measurement. DATA EXTRACTION: Two independent reviewers extracted study data and assessed study quality using the QUADAS-2 (Quality Assessment of Diagnostic Accuracy Studies 2) tool. DATA SYNTHESIS: Sixteen studies (n = 3356 patients) that evaluated semiquantitative or quantitative POC tests and used random urine samples collected in primary or secondary ambulatory care settings met inclusion criteria. Pooling results from a bivariate random-effects model gave sensitivity and specificity estimates of 76% (95% CI, 63% to 86%) and 93% (CI, 84% to 97%), respectively, for the semiquantitative test. Sensitivity and specificity estimates for the quantitative test were 96% (CI, 78% to 99%) and 98% (CI, 93% to 99%), respectively. The negative likelihood ratios for the semiquantitative and quantitative tests were 0.26 (CI, 0.16 to 0.40) and 0.04 (CI, 0.01 to 0.25), respectively. LIMITATION: Accuracy estimates were based on data from single-sample urine measurement, but guidelines require that diagnosis of albuminuria be based on at least 2 of 3 samples collected in a 6-month period. CONCLUSION: A negative semiquantitative POC test result does not rule out albuminuria, whereas quantitative POC testing meets required performance standards and can be used to rule out albuminuria. PRIMARY FUNDING SOURCE: None.